SWOT Analysis of the Financial Model to Support Decarbonization of Shipping in Indonesia - Zulfakhri, Ahlan (CV. Ulil Albab Corp, 2025)
This study analyzes a financial model to support the decarbonization of shipping in Indonesia using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. The research identifies that Indonesia has strengths in the variety of financing sources, including a joint financing scheme (65% from banks, 30% from non-bank financial institutions, and 5% equity) and a supporting institutional structure. However, there are significant weaknesses, such as high financing costs with interest rates ranging from 7% to 12% per year and limited government support, as ships and shipyards are not considered critical infrastructure. Development opportunities are identified through financing innovations, such as green financing and the implementation of the Poseidon Principles, as well as potential international collaborations and capital market development. Key threats include global economic uncertainty, challenges in implementing decarbonization standards, and competition from countries with more attractive financing schemes. The study concludes that there is a need for supportive policy development, financing scheme innovations, and strengthened collaboration among stakeholders to create an effective financial model that supports the transition to more environmentally friendly shipping in Indonesia.